2018
DOI: 10.1002/hbm.24463
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of field strength, total intracranial volume, sex, and age effects on the goodness of harmonization for volumetric analysis on the ADNI database

Abstract: When analyzing large multicenter databases, the effects of multiple confounding covariates increase the variability in the data and may reduce the ability to detect changes due to the actual effect of interest, for example, changes due to disease. Efficient ways to evaluate the effect of covariates toward the data harmonization are therefore important. In this article, we showcase techniques to assess the "goodness of harmonization" of covariates. We analyze 7,656 MR images in the multisite, multiscanner Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 104 publications
(169 reference statements)
0
46
1
Order By: Relevance
“…Though much of the early studies on how brain areas change in size over the lifespan utilized crosssectional data, there has been an increase in the number of studies using longitudinal data collection. One caution on relying on estimates based on cross-sectional data alone is the variability added due to differences in scanner properties and the sex of the subjects [26,27]. Though the current analysis focused on cross-sectional data, there has been good consistency found in the estimated rate of change when cross-sectional data was compared to longitudinal data in older adults ( [3,14] though see [28]).…”
Section: Discussionmentioning
confidence: 91%
“…Though much of the early studies on how brain areas change in size over the lifespan utilized crosssectional data, there has been an increase in the number of studies using longitudinal data collection. One caution on relying on estimates based on cross-sectional data alone is the variability added due to differences in scanner properties and the sex of the subjects [26,27]. Though the current analysis focused on cross-sectional data, there has been good consistency found in the estimated rate of change when cross-sectional data was compared to longitudinal data in older adults ( [3,14] though see [28]).…”
Section: Discussionmentioning
confidence: 91%
“…2.8 | Assess the effect of demographic-and scanner-related variables on MRDATS It has been shown that both demographic-related (sex and age) as well as the scanner-related (field strength) variables might influence the outcomes of an analysis involving MRI-based volume features (Ma, Popuri, et al, 2019). Therefore, we explored the effect of demographic-related (sex and age) as well as the scanner-related variables (field strength) on…”
Section: Comparison Between Mrdats With Csf Biomarkermentioning
confidence: 99%
“…Finally, in the feature extraction and normalization step, the volume of each patch was extracted as a primary feature for disease classification. The w-score, which represents the standardized residual of the chosen features, was computed to remove the effect of covariates such as the field of strength (1.5T or 3T), scanner type, scanning site, age, sex, and the size of the intra-cranial vault (ICV) of each individual (Ma et al, 2018 andPopuri et al, 2020). The normalized features as represented by the w-scores were input into the classifier.…”
Section: Multi-level Multi-type Feature Extractionmentioning
confidence: 99%
“…The locally-clustered cortical patches were then propagated back to each of the target space following the backward deformation field that was derived during the LDDMM non-rigid registration step (Beg et al, 2005). The average thickness of the mantle within each patch was computed as features followed by the w-score normalization (Ma et al, 2018 andPopuri et al, 2020) to remove the confounding effect of covariates.…”
Section: Multi-level Multi-type Feature Extractionmentioning
confidence: 99%